Dilema Pembentukan Karakter Siswa dalam Penerapan Kurikulum Merdeka - Sasmita Sari, Ajeng Yuri Eka; Hadi, Nur; Rozuli , Ahmad Imron; Purba, Dano (Pustaka Peradaban, 2024)
This study examines the impact of curriculum system changes on student behavior and character patterns at SMA Negeri 2 Batu, Kota Batu, related to the transition from Curriculum 13 to the Merdeka Curriculum. The Merdeka Curriculum is part of the Merdeka Belajar program, which aims to provide freedom to educational units, teachers, and students to develop their potential to the fullest. The results show that students face complex dilemmas. Although project-based learning in the Merdeka Curriculum offers a deeper learning experience, students face various challenges such as high workloads, risk of stress, and the